Biosynthesis of Se nanoparticles and its effect on UV-induced DNA damage - Prasad, Kumar Suranjit; Patel, Hirnee; Patel, Tirtha; Patel, Khusbu; Selvaraj, Kaliaperumal (Colloids and Surfaces B-Biointerfaces, 2013)
This paper reports, an environmentally benign procedure of synthesis and characterizations of selenium nanoparticles and their protective effect against UV-induced DNA damage activities. An aqueous leaf extract of lemon plant was used as a precursor for synthesis of colloidal selenium nanoparticles. Resulting nanoparticles were characterized using UV-vis spectrophotometer, photoluminescence, TEM, EDAX, FT-IR and XRD, respectively. Selenium colloidal solution exhibited an absorption maximum at 395 nm and produced an emission maximum at 525 nm. Transmission electron microscopy followed by selected area electron diffraction pattern analysis indicated the formation of spherical, polydispersed, crystalline, selenium nanoparticles of diameter ranging from (similar to 60 to 80 nm). X-ray diffraction studies showed the formation of 111, 2 0 0 and 220 planes of face-centered cubic (fcc) selenium. EDAX analysis confirmed the presence of selenium in nanosphere. Fourier transformed infrared spectroscopic investigation reveled the involvement of carboxyl (-C=0), hydroxyl (-OH), amine (-NH) functional group of lemon plant extract in preparation of selenium nano particles. MU assay as well single cell gel electrophoresis assay or comet assay revealed that synthesized selenium nanoparticles, caused less cell death of lymphocytes and prevented DNA damage, when cells were exposed to UVB. The fluorescent property of selenium nanopartides can be used as diagnostic agent. Further, their anti DNA damaging property can be investigated as a chemotherapeutic agent in cancer therapy. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Comet assay; EDAX; FT-IR; MTT assay; Selenium nanoparticles; UV-vis spectrophotometer

Biogenic synthesis of selenium nanoparticles and their effect on as(III)-induced toxicity on human lymphocytes - Prasad, Kumar Suranjit; Selvaraj, Kaliaperumal (Biological Trace Element Research, 2014)
{A bioreductive capacity of a plant, Terminalia arjuna leaf extract, was utilized for preparation of selenium nanoparticles. The leaf extract worked as good capping as well as stabilizing agent and facilitated the formation of stable colloidal nanoparticles. Resulting nanoparticles were characterized using UV-Vis spectrophotometer, transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDAX), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction analysis (XRD), respectively. The colloidal solution showed the absorption maximum at 390 nm while TEM and selected area electron diffraction (SAED) indicated the formation of polydispersed, crystalline selenium nanoparticles of size raging from 10 to 80 nm. FT-IR analysis suggested the involvement of O-H, N-H
Keywords: Arsenite; Comet assay; EDAX; MTT assay; Selenium nanoparticles; Terminalia arjuna